MOLECULAR DOCKING OF £6.ANHYDROERYTHROMYCINTO rRNA23S Deinococcus radiodurans AND THE PREDICTIONOF ITS ANTIBIOTIC POTENCY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT ,16-anhidroeritromisin-Ais a new derivative of erythromycin which is synthesized through biosynthetic engineering technique. The molecular docking in rRNA 235 Deinoccocus radiodurans are accomplished to determine the model and strength of binding to the target macromolecule. The molecular docking of erythromycin-A and 6-deoksieritromisin-A to the same macromolecule is used as a control. The docking result of the ,16_ anhidroeritromisin-A shows that it occupies the same cavity as of the experimental erythromycin-A in the same macromolecule. The binding position of ,16-anhidroeritromisin-Ais not exactly same as erythromycin-A and 6- deoksieritromisin-A due to the presence of ,16unsaturated double bond. However the hydroxyl group(OH) at C-6 does not have an apparent effect on the binding model to rRNA235 D. radiodurans.